Sustainable Bioethylene Production from Lignocellulosic Bioethanol: Performance of Zeolitic Catalysts and Mechanistic Insights - Mendieta, Carolina Mónica (2025)
Producing second-generation (2G) bioethylene through the dehydration of 2G bioethanol is a challenge, requiring the effective use of catalysts as an alternative to fossil-based ethylene production. This work evaluates the production of bioethylene from the catalytic dehydration of 2G bioethanol [from pine sawdust produced via a simultaneous saccharification and fermentation SSF process (53%)] using γ-Al2O3; ZSM-5, NH4 +Y, H-ZSM-5, and H-Y zeolite as catalysts. Yields of 94.6% (at 372 ◦C) and 85.5% (at 473 ◦C) of 2G bioethylene were obtained when using H-ZSM-5 and H-Y zeolite, respectively. These results demonstrate that the H-ZSM-5 zeolite showed the best performance for 2G bioethanol dehydration, producing high 2G bioethanol conversion and 2G bioethylene selectivity at a lower reaction temperature. Ethylene production from the catalytic dehydration of commercial (96%) and diluted (53%) ethanol was evaluated as a reference, along with the effects of the weight hourly space velocity (WHSV) and ethanol concentration. Varying the WHSV from 2.37 to 4.73 h−1 at 312 ◦C and using commercial ethanol at 96%, produced similar ethanol conversion of 100% and ethylene yield of 100%. At 290 ◦C, with a WHSV of 2.37 h−1 and 53% diluted commercial ethanol, H-ZSM-5 converted 76.83% of the ethanol and produced a 75.8% ethylene yield. A study based on density functional theory (DFT) has shown that diethyl ether is a key intermediate in the conversion mechanism on H-ZSM-5, proceeding through an ethoxide intermediate in the rate-determining step, with an apparent activation energy of 25.4 kcal mol−1.